Prevalence of preoperative diagnostic of hepatocellular carcinoma in liver transplant recipients, at Hospital Santa Isabel in Blumenau-SC in the year 2008, and association with the diagnostic confirmation by anatomopathological examination - Bertoldo, Rodrigo (2021)
Hepatocellular carcinoma (HCC) is the most prevalent liver cancer in humans. In recent decades, it has been witnessed an increasing incidence of such tumor due to the increasing amount of individuals infected with hepatitis C virus (HCV) and the increase of survival of cirrhotic patients. Some of the tools used to detect HCC are ultrasound (US), computed tomography (CT) and serum alpha-fetoprotein dosage (SAFP). Liver transplantation can be used as therapeutic measure of HCC in cirrhotic patients with tumor restricted to the liver and at an early stage. Purposes: To assess the preoperative prevalence of hepatocellular carcinoma in liver transplant recipients according to the EASL (European Association for the Study of the Liver) criteria and to associate it with the diagnostic confirmation by anatomopathological examination at the Department of Liver Transplantation at Hospital Santa Isabel in Blumenau-SC along. Methods: Clinical data were retrospectively analyzed from 71 liver transplant recipients, emphasizing the etiology of the liver transplantation indication, the serum preoperative AFP and the anatomopathological analysis of the explanted organs. Results: Preoperative prevalence of HCC was 26.76%. When considering values of the alpha-fetoprotein levels ≤ 20 ng/mL as normal, it can be found 63.16% sensitivity of such diagnostic method. In 73.68% cases, preoperative diagnosis of HCC was confirmed by anatomopathological analysis of the explanted organs. Conclusion: Both the prevalence of preoperative HCC according to the EASL criteria, such as prevalence of anatomopathological of the HCC explanted organs was higher than that reported in other studies, possibly due to the increasing cases of infection by hepatitis C occurred in recent years due to the increase in the survival of patients with cirrhosis and by the implementation since 2006 of the criterion set by the MELD score according to the Administrative Rule No. 1160 of 29 May, 2006. The prevalence of incidentalomas and the diagnosis of the serum level sensitivity for AFP were similar to those found by other authors. The HCC diagnostic confirmation occurred in 73.68% cases due to the limitation of the diagnostic tests.